Home or Away? : Profit Shifting with Territorial Taxation - Langenmayr, Dominika; Liu, Li. (Washington, D.C. : International Monetary Fund, 2022)
In 2009, the United Kingdom abolished the taxation of profits earned abroad and introduced a territorial tax system. Under the territorial system, firms have strong incentives to shift profits abroad. Using a difference-in-differences research design, we show that the profitability of UK subsidiaries in low-tax countries increased after the reform compared to subsidiaries of non-UK multinationals in the same countries by an average of 2 percentage points. This increase in profit shifting also leads to increases in measured productivity of the foreign affiliates of UK multinationals of between 5 and 9 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Taxes and Subsidies; International Business; International Fiscal Issues; International Public Goods; Multinational Firms